2008
DOI: 10.1002/ptr.2527
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory effect of the ethanol extract of Berberis koreana in a gerbil model of cerebral ischemia/reperfusion

Abstract: Berberis koreana extract (BE) has a strong neuroprotective effect after ischemic stroke in gerbils, which is associated with the inhibition of the N-methyl-d-aspartate receptor. The present study examined the antiinflammatory mechanism of BE after ischemic damage in vitro and in vivo. The BE used contained on average 7.39 +/- 0.78 mg/g of berberine. In PC12 cells with inflammation, prostaglandin E2 (PGE2) production was significantly reduced by BE. About 75% of pyramidal cells in the hippocampal CA1 region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…ber of reports, Coptis japonica Makino and its components, berberine, have been used to control airway allergic or infl ammatory diseases and reported to have anti-infl ammatory and anti-cancer effects (Yoo et al, 2008;Sun et al, 2009;Tang et al, 2009). On the other hand, it was previously reported that berberine stimulated basal mucin release from airway goblet cells, by our group .…”
Section: Introductionmentioning
confidence: 80%
“…ber of reports, Coptis japonica Makino and its components, berberine, have been used to control airway allergic or infl ammatory diseases and reported to have anti-infl ammatory and anti-cancer effects (Yoo et al, 2008;Sun et al, 2009;Tang et al, 2009). On the other hand, it was previously reported that berberine stimulated basal mucin release from airway goblet cells, by our group .…”
Section: Introductionmentioning
confidence: 80%
“…It appears that khellin extracts have some antimicrobial activity; this might be attributable to both the khellin and visnagin constituents, which both seem to have antifungal, antibacterial, and antiviral activity [25]. In addition, several reports have demonstrated that drugs or compounds having an anti-inflammatory effect can show a neuroprotective effect [4,26,27]. Thus, we examined the effect of visnagin on proinflammatory mediators expression induced by KA.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's (Zhu and Qian, 2006), forebrain ischemia (Yoo et al, 2006), mental depression (Kulkarni and Dhir, 2008), anxiety (Peng et al, 2004), etc. Berberine (7.45 ± 0.85 mg/g) has been identifi ed to reverse N-methyl-d-aspartate (NMDA)-induced excitotoxicity when tested in gerbil hippocampal neurons (Yoo et al, 2008). In one study, it has been demonstrated that berberine (1 or 2 mg/kg., p.o.)…”
Section: Berberine In Cns Disordersmentioning
confidence: 98%
“…An interesting study has demonstrated the protective action of the extract of Berberis koreana (contains an average of 7.39+/−0.78 mg/g berberine) in a gerbil model of cerebral ischemia/reperfusion. It was hypothesized that the anti-infl ammatory activity of berberine may be responsible for the neuroprotective action in cerebral ischemia (Yoo et al, 2008). It has been demonstrated that berberine (20 mg/kg/day for 1, 3, or 5 days) reduced the platelet aggregation and thromboxane levels (a powerful platelet aggregator) in rats, which may be partly responsible for its neuroprotective action in animal models of cerebral ischemia (Wu and Liu, 1995).…”
Section: Cerebral Ischemiamentioning
confidence: 99%
See 1 more Smart Citation